IMPACT OF VENEER LAYOUTS ON PLYWOOD BENDING PROPERTIES (Innovation in Woodworking Industry and Engineering design, 2026)
The research presented in this paper includes the study of the plywood bending properties through a change of the position of the layers in the structure of the panel around the central axis, without changing the number and the thickness of the veneers. For studying this impact, experimental models of nine-layer plywood are made. The models are made from peeled beech veneers with thickness of 1,2; 1,5; 2,2 and 3,2 mm. The modeling is made on the basis of changing the position of veneers with thickness of 3,2 mm around the central axis (axis of symmetry). Pure water-soluble phenol-formaldehyde resin is used as plywood binder. The bending strength and modulus of elasticity in bending of the plywood panels is tested in two directions, parallel and perpendicular to the face grain. The research results showed that the tested plywood models meet the defined values of bending properties in accordance with the requirements of the MKS standard for structural plywood for use in construction. The different layouts of veneer sheets in panel structure gives opportunities for production of panels with different strength characteristics.